SLEEPING PATTERNS AND ONLINE GAMING HABITS: UNRAVELLING THEIR INFLUENCE ON ANGER TOLERANCE AMONG UNIVERSITY STUDENTS: Anger tolerance among university students - Islam, Md. Muzahid; Mimi, Afshana; Khatun, Murshida; Islam, Tafajjal; Al Based, Md. Abdullah; Sarker, Pramath Chandra (Universitas Airlangga, 2025)
Introduction: The relationship between students' tolerance for anger and their daily gaming habits significantly affects their emotional and academic well-being. Excessive gaming can contribute to increased anger issues and negative psychological outcomes, which individual sleep patterns may also influence. This study aims to develop effective strategies for emotional regulation and mental well-being by examining the impact of sleep duration and online gaming on students' ability to manage anger. Method: This cross-sectional research design involved 149 students from various departments at Rajshahi University, selected based on gender and place of residence. The study utilized the Anger Tolerance Scale (ATS). Participants were chosen through convenience sampling, and data were collected using questionnaires. Correlation analysis was performed, and data analysis was conducted using SPSS Statistics. The study achieved a Cronbach's alpha of 0.82, indicating acceptable internal consistency. Results: The findings indicated a positive correlation between daily sleep hours and anger tolerance, while daily gaming habits negatively impacted this tolerance. Additionally, less sleep was linked to more time spent playing online games. Conclusions: The study found that students' anger tolerance is closely tied to sleep patterns and gaming habits. Insufficient sleep and excessive gaming hinder effective anger management. These findings highlight the need to evaluate sleep and gaming behaviors to help students manage emotions, offering insights for mental health professionals and educational institutions.